The heavenly book motif in Judeo-Christian apocalypses 200 BCE-200 CE. (Supplements to the Journal for the Study of Judaism, 2011)
Books and writing, according to Jacques Derrida, are always concerned with questions of life and death. Nowhere is this more true than regarding the heavenly book motif, which plays an important role in early Judeo-Christian literature, and particularly in apocalypses. This book identifies four sub-types of the motif-the books of life, deeds, fate, and action-and examines their development and function primarily in Jewish and Christian apocalypses. It argues that the overarching function of the motif is to signify life and death for those inscribed: earthly life and death in its early appearances and eternal destiny in later texts. The first full-length analysis of the heavenly book motif in English, this study highlights a vital element of the genre apocalypse.